Proceedings of the second Jordanian Conference for Mechanical Engineering - Jordanian International Conference for Mechanical Engineering (2nd : 1997 : Amman, Jordan) (Arabia : The Organizing Committee, 1997)
Vol.1. Energy and environment, refgeration and airconditioning -- Vol.2. Manufacturing processes, materials, industrial production and maintenance